2020
DOI: 10.29313/amwaluna.v4i1.5094
|View full text |Cite
|
Sign up to set email alerts
|

Indeks Inklusi Keuangan Syariah di Indonesia

Abstract: This research is based on the problem is the low involvement of the public in making transaction using Islamic banking service in Indonesia. This study aims to describe and measure the level of Islamic financial inclusion on the Islamic banking sector include Sharia Commercial Bank (BUS), Sharia Business Unit (UUS) and Rural Sharia Bank (BPRS) in Indonesia period 2015-2018 using Index of Financial Inclusion. There are three dimensions measured in this study dimensions of accessibility, availability and usage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 0 publications
1
14
0
5
Order By: Relevance
“…A survey by Otoritas Jasa Keuangan (OJK) revealed that the percentage of Indonesia's population who are Islamically financially literate was only 8.93 per cent in 2019 (OJK, 2017;Puspaningtyas, 2019). This percentage is far below conventional financial literacy which stood at 37.72 per cent (Puspaningtyas, 2019;OJK, 2019). This factor influences the index of public access to Islamic financial products and services (i.e., Islamic financial inclusion).…”
Section: Introductionmentioning
confidence: 99%
“…A survey by Otoritas Jasa Keuangan (OJK) revealed that the percentage of Indonesia's population who are Islamically financially literate was only 8.93 per cent in 2019 (OJK, 2017;Puspaningtyas, 2019). This percentage is far below conventional financial literacy which stood at 37.72 per cent (Puspaningtyas, 2019;OJK, 2019). This factor influences the index of public access to Islamic financial products and services (i.e., Islamic financial inclusion).…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, Islamic financial inclusion in Indonesia only reached 0.122 and in 2015 it increased to 0.127 (Umar, 2017). Then in 2018, the sharia financial inclusion index in Indonesia increased become 0.180 level (Puspitasari et al, 2020). Based on the results of a national survey of sharia financial literacy conducted by OJK in 2016, Aceh Province has the highest sharia financial inclusion in Indonesia at the level of 8.1%.…”
Section: Introductionmentioning
confidence: 99%
“…The low of Islamic financial inclusion in the city of Pekanbaru is still understandable because Pekanbaru is a part of Riau Province, where the Islamic financial inclusion index of Riau Province is classified as low at 0.080 level and ranks 20th out of 33 provinces in Indonesia (Ali et al, 2019). Factors contributing to the low index of Islamic financial inclusion in Riau Province are accessibility which only reached 0.05, usage by 0.07, and availability by 0.28 (Puspitasari et al, 2020). With the inclusiveness of Islamic finance at a wider MSME, it is expected to be able to improve the welfare of the community and business people.…”
Section: Introductionmentioning
confidence: 99%
“…Survei Nasional Literasi dan Inklusi Keuangan pada tahun 2016 memberikan data indeks inklusi keuangan syariah sebesar 11,1%, yang artinya dari setiap 100 penduduk Indonesia, hanya 11 orang yang memanfaatkan produk dan layanan jasa keuangan syariah. Pada penelitian Puspitasari et al (2020) yang membahas perhitungan inklusi keuangan syariah pada 33 provinsi di Indonesia menunjukkan bahwa tingkat inklusi keuangan syariah pada Tahun 2015-2018 mengalami perkembangan yang fluktuatif, rata-rata Indeks Inklusi Keuangan Syariah di Indonesia termasuk kategori rendah. Pemerintah memberikan perhatian besar dalam rangka upaya peningkatan pangsa pasar dan inklusi keuangan, Buku Pedoman Strategi Literasi Nasional Keuangan Indonesia menjadi salah satu implementasi kebijakan pemerintah dalam meningkatkan perkembangan Bank Syariah melalui peningkatan kompetensi sumber daya manusia.…”
Section: A Pendahuluanunclassified